Biological Productivity in Laterite Areas of Southern Bengal - Chakrabarti, Kalyan (Indian Forester, 1993)
The analysis of the designed experiment tends to indicate that there is a significant effect of spacing on biological productivity in the laterite areas of West Bengal. The closer is the spacing, more is the biomass productivity for the plots in both the locations of Southern Bengal. Regarding intra-species productivity, Eucalyptus was observed to produce more biomass productivity than species like Acacia auriculiformis, Cassia siamea, Gmelina arborea, Dalbergia sissoo and Lellcaena leucocephala and this order of productivity is markedly visible in both the locations of Southern Bengal. A descending order of productivity was noticed in these six species for different kinds of spacing treatments. This study brings out a code of treatment ethics and procedural discipline in spacing treatments for laterite areas of West Bengal and the results of this study may be compared with other similar sites to comprehend the in-vivo biological properties.